2020
DOI: 10.32615/ps.2019.147
|View full text |Cite
|
Sign up to set email alerts
|

Special issue in honour of Prof. Reto J. Strasser - Chlorophyll a fluorescence parameters as indicators of a particular abiotic stress in rice

Abstract: The aim of this study was to evaluate the validity of some chlorophyll (Chl) a fluorescence parameters as early indicators of a particular abiotic stress and also to characterize the effect of different abiotic stresses [high light, NaCl, polyethylene glycol (PEG)-induced osmotic stress, and heavy metals] on the electron transport chain of rice (Oryza sativa L.) seedlings. The results clearly revealed that Chl a fluorescence parameters differ between abiotic stress types and also allowed us to select some para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 54 publications
11
79
0
Order By: Relevance
“…The F v /F m , which is one of the parameters of prompt chlorophyll fluorescence, was determined after dark adapt for 20 min. Previous study revealed that F v /F v in plant effectively responded to NaCl, PEG, light, and heavy metal stress [34]. In this study, Fv/Fm values in the PEG-treated seedlings declined significantly with raising osmotic level, while the decrease of Fv/Fm in the NaCl-treated group was only observed at level 3 (300 mM NaCl) ( Figure 2).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The F v /F m , which is one of the parameters of prompt chlorophyll fluorescence, was determined after dark adapt for 20 min. Previous study revealed that F v /F v in plant effectively responded to NaCl, PEG, light, and heavy metal stress [34]. In this study, Fv/Fm values in the PEG-treated seedlings declined significantly with raising osmotic level, while the decrease of Fv/Fm in the NaCl-treated group was only observed at level 3 (300 mM NaCl) ( Figure 2).…”
Section: Discussionsupporting
confidence: 52%
“…Suriyan and Chalermpol [46] revealed NPQ and proline in leaves of plant responded to the iso-osmotic levels, and different dynamics of ChlF were also observed. ChlF parameters were well applied to monitoring plant response to various abiotic stresses [33,34], but it was still difficult to distinguish between drought and salinity stress by ChlF [37].…”
Section: Discussionmentioning
confidence: 99%
“…Typical symptoms of heat damage include accelerated senescence and significant decline in photosynthesis [ 17 ]. It has been proved that chlorophyll a fluorescence parameters could act as important indicators of abiotic stress [ 18 ]. The study of [ 19 ] found that heat stress caused damage to photosystem II leading to significant decline in Fv/Fm, but plants could switch photosystem through driving cyclic electron flow for adapting to heat environment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, strengthened NPQ is an important adaptive mechanism to N insufficiency in rice. Faseela et al [49] demonstrated chlorophyll fluorescence parameters could be as indicators of a particular abiotic stress in rice. The low N obviously altered the leaf structure in both cultivars.…”
Section: Mechanism Of Acclimation To N Insufficiencymentioning
confidence: 99%